Moral responsibility and the flicker of freedom - Capes, Justin A. (Oxford University Press, 2023)
In Moral Responsibility and the Flicker of Freedom, Justin A. Capes challenges that thought experiments such as the sort devised by Harry Frankfurt are counter examples to the principle that a person is morally responsible for what he did only if he could avoid doing it. He argues that, far from being counterexamples to the principle, Frankfurt cases, as they have come to be known, actually provide further confirmation of it, a conclusion that has important implications for our understanding of free will and moral responsibility